1999
DOI: 10.1515/corrrev.1999.17.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behaviour of Prestressed Steel-Reinforced Structures

Abstract: A relationship between the corrosion damage and the loss of prestressing load on concrete prestressed metallic structures is proposed after experimental data. Mathematically, the first natural frequency change is related to the reduction on the prestressing load, and as a result, to the corrosion effect. In general, it has been found that the reduction on the prestressing load due to corrosion has a cracking type behaviour with a small variation rate at the beginning and a larger one at the end of the corrosiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In investigating the configuration of corroded reinforcing steel bars, many researchers considered that the stress level has no effect on pit development (Carrion-Viramontes et al, 1999;Darmawan and Stewart, 2007;Evans, 1957) and suggested that a low degree of plastic deformation does not influence the corrosion rate (Apostolopoulos and Papadakis, 2007). However, Trejo et al (2009) recently found that the in-service stress level had a statistically significant influence on the corrosion activity and tension capacity of post-tensioning strands.…”
Section: Introductionmentioning
confidence: 99%
“…In investigating the configuration of corroded reinforcing steel bars, many researchers considered that the stress level has no effect on pit development (Carrion-Viramontes et al, 1999;Darmawan and Stewart, 2007;Evans, 1957) and suggested that a low degree of plastic deformation does not influence the corrosion rate (Apostolopoulos and Papadakis, 2007). However, Trejo et al (2009) recently found that the in-service stress level had a statistically significant influence on the corrosion activity and tension capacity of post-tensioning strands.…”
Section: Introductionmentioning
confidence: 99%